Promotion of Alcohol Production using high Gravity Fed-Batch Alcoholic Fermentation through Novel Yeast Strain - Misale, Govind; Neelgund, S. E.; Patil, S. V.; Singh, Vijendra (International Journal of Scientific Research in Biological Sciences, 2018)
Fermentation is well known biological process to produce the alcohol by using raw materials as molasses, grains etc. The performance of molasses based distilleries are day by day improved towards high efficiency, lowest sugar loss and high yield. In many distilleries, earlier and at present the operation mode of fermentation process is “batch fermentation” which gives the less efficiency 80 to 85 % with poor quality alcohol and spent wash generation is about 8 to 15 lit/lit of alcohol produced. Later on it is developed as “continuous fermentation” which gives high efficiency 88 to 90% and with better quality of alcohol and spent wash generation is about 3 to 4 lit/lit of alcohol produced by adopting spent wash recycle to fermenter and treatment of spent wash in integrated evaporation with distillation system. But In India distilleries effluent i.e., spent wash has high organic load which causes Major water pollution so these industries are comes under “Red category” and it is necessary to improve this process and reduce the spent wash generation as much as possible along with high fermentation efficiency and less energy consumption for separation of alcohol in downstream process of distilleries. So this presentation is to introduce the new mode of operation named as “High gravity Fed- batch alcoholic fermentation” of cane molasses. The pilot trial is taken by using the developed yeast stain “Scizosacharomyces Pombe-Fed” with upgraded feeding pattern. Process parameters are experimented and studied in “Shree Renuka Sugars Ltd. Havlaga unit” and the results high efficiency of about 89 to 90 % and high yield of alcohol in fermented wash of about 11.8 to 12.5% so as to reduce the spent wash generation is about 2.2 to 2.4 lit/lit of alcohol produced which will helps to achieve one of the strict norm of Pollution Control board “Zero liquid Discharge” with post treatment of Bio-composting and incineration of high brix spent wash(55 to 60 % Solids) in specially designed boiler